Promoting healthy bonds between adolescent mothers and their babies: a intervention experience - Traverso Koroleff, Pierina (2010)
We performed an intervention program aimed at promoting a healthy relationship between teenage mothers and their babies, with 26 mothers between 15 and 19 years old, who have one son or daughter between 0 and 6 months old. They were from a poor area of Lima, Peru. The intervention was conducted in four groups, each of which had ten sessions. We assessed the interaction between mother and baby, the mother’s interpretation of emotions and the maternal representations (a description of the baby, of herself as a mother and of the relationship between them), before and after the program. The same evaluations were performed with a comparison group of 18 young mothers with the same characteristics. The article presents and discusses the results of both evaluations.